Implementation of Event Management System Based on Campus Event Man-agement Information System As “Sistem Informasi Manajemen Acara Kampus” (SEMARAK) - Rizka Hadiwiyanti; Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo (Future Science, 2020)
Within a year, Universitas Pembangunan Nasional